Urea-Triazone N Characteristics and Uses - John G. Clapp (The Scientific World Journal)
Urea-triazone nitrogen (N) is a stable solution resulting from a controlled reaction in aqueous medium of urea, formaldehyde, and ammonia which contains at least 25% total N. This N source contains no more than 40%, nor less than 5%, of total N from unreacted urea and not less that 40% from triazone. All other N shall be derived from water-soluble dissolved reaction products of the above reactants. It is a source of slowly available N. The rate of mineralization of urea-triazone is about 66% that of urea after 8 days when incorporated in a Munjor sandy loam. Ammonia volatilization losses of N applied as urea-triazone were about 41% of those from urea on a Cecil sandy loam in the first week after application. N leaching losses through saturated Yolo loam columns of urea-triazone were about two thirds that of urea or nitrate N. This N source has proven to be a safer and more effective material for direct application on plant foliage. Tomato growth was enhanced with foliar application of urea-triazone relative to that obtained from ammonium nitrate or urea. The stability of this N source from potential losses via ammonia volatilization and nitrate leaching when soil applied is also documented by results from university trials.